2015
DOI: 10.7314/apjcp.2015.16.14.5933
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Baseline Neutrophil-Lymphocyte and Platelet-Lymphocyte Ratios in Local and Advanced Gastric Cancer Patients

Abstract: Background: We aimed to investigate the prognostic value of baseline neutrophil, lymphocyte, and platelet counts along with the neutrophil-lymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR) in local and advanced gastric cancer patients. Materials and Methods: In this retrospective cross-sectional study, a total of 103 patients with gastric cancer were included. For all, patient characteristics and overall survival (OS) times were evaluated. Data from a complete blood count test including neutrophil, ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 35 publications
1
23
1
1
Order By: Relevance
“…In contrast with the previously described findings, NLR was not informative regarding survival of gastric cancer patients having only local disease while it was significantly associated with survival in advanced cases [56]. Some negative findings, including the cited one, can be explained by small study group comprising only 53 patients with local disease and 50 with advanced cancer [56].…”
Section: Nlr and Survival: Prognostic Implicationscontrasting
confidence: 74%
See 2 more Smart Citations
“…In contrast with the previously described findings, NLR was not informative regarding survival of gastric cancer patients having only local disease while it was significantly associated with survival in advanced cases [56]. Some negative findings, including the cited one, can be explained by small study group comprising only 53 patients with local disease and 50 with advanced cancer [56].…”
Section: Nlr and Survival: Prognostic Implicationscontrasting
confidence: 74%
“…Interestingly, high platelet count was associated with better overall survival in patients having local disease [56].…”
Section: Plr and Survival: Prognostic Implicationsmentioning
confidence: 98%
See 1 more Smart Citation
“…As in Aldemir's study [24], the GC patients were included as early stage and advanced stage independently, therefore, the two cohorts were extracted separately and named as Aldemir1 and Aldemir2. The selection process of the included studies was shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The 14 cohorts included 6,280 GC patients. Eight cohorts [14, 21, 23, 25, 27, 2931] were performed in China, four cohorts [22, 24, 26] were conducted in Turkey and two cohorts [20, 28] were carried out in Korea. The sample sizes ranged from 50 to 1,986.…”
Section: Resultsmentioning
confidence: 99%